2005
DOI: 10.1002/jcb.20583
|View full text |Cite
|
Sign up to set email alerts
|

During male pronuclei formation chromatin remodeling is uncoupled from nucleus decondensation

Abstract: Male pronucleus formation involves sperm nucleus decondensation and sperm chromatin remodeling. In sea urchins, male pronucleus decondensation was shown to be modulated by protein kinase C and a cdc2-like kinase sensitive to olomoucine in vitro assays. It was further demonstrated that olomoucine blocks SpH2B and SpH1 phosphorylation. These phosphorylations were postulated to participate in the initial steps of male chromatin remodeling during male pronucleus formation. At final steps of male chromatin remodeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
(30 reference statements)
0
10
0
Order By: Relevance
“…As reported before, the SpH-protease characterized in our laboratory was able to efficiently degrade the five SpH in vitro and in vivo [Imschenetzky et al, 1997;Monardes et al, 2005]. However, it was unknown if the SpH may be degraded while forming nucleosomes or if alternatively, the histones should be released from DNA prior to their degradation.…”
Section: Sperms-nucleosomes Disassembly Is a Prerequisite For Histonementioning
confidence: 74%
See 1 more Smart Citation
“…As reported before, the SpH-protease characterized in our laboratory was able to efficiently degrade the five SpH in vitro and in vivo [Imschenetzky et al, 1997;Monardes et al, 2005]. However, it was unknown if the SpH may be degraded while forming nucleosomes or if alternatively, the histones should be released from DNA prior to their degradation.…”
Section: Sperms-nucleosomes Disassembly Is a Prerequisite For Histonementioning
confidence: 74%
“…Consistent with the independence of male chromatin remodeling from the proteins newly synthesized after fertilization [Poccia et al, 1981;Imschenetzky et al, 1991], this protease was found as an inactive precursor in the nucleus of unfertilized eggs and shown to be activated and mobilized into male pronucleus after fertilization [Concha et al, 2005a]. The role of this protease in SpH degradation was further supported by the persistence of the complete set of SpH at the end of the initial cell cycle in zygotes treated with E-64-d, an inhibitor of cysteine-proteases [Monardes et al, 2005]. Based on this evidence we proposed a model in which this SpH-protease exhibits a crucial role in male chromatin remodeling after fertilization [Imschenetzky et al, 2003].…”
mentioning
confidence: 81%
“…Fluorescent signals were observed by epifluorescence Nikon Eclipse E-600 microscope using a filter G-2F/C. To visualize the nucleus, the samples were stained with 1 mg/ml DAPI as previously described [Monardes et al, 2005].…”
Section: Immuno-staining and Microscopymentioning
confidence: 99%
“…H2A and H2B transcript variants have a different structure in the N-terminal chain of the transcripts (Frank et al 2003). TH2B is a testis-specific transcript variant of the H2B histone, which has differences in the structure of three phosphorylation sites (Ser 12, Thr 23 and Thr 34) (Green 2001;Monardes et al 2005). As a result there are different combinatorial interactions between serine and threonine residues which could be a reason for the specific pattern of acetylation and methylation (Rousseaux et al 2005).…”
Section: Chromatin Structure In Mammalian Spermmentioning
confidence: 99%